Teacher’s Perception on Implementation of Content and Language Integrated Learning (CLIL) in the Primary School - Nur Aflahatun; Januarius Mujiyanto; Sri Wuli Fitrianti (Universitas Negeri Semarang, 2022)
Content and Language Integrated Learning (CLIL) as one of approach that create an educational environment in English that promotes “internationalization at home” in schools has inspired many multilingual learnings. This much-appreciated stimulation is expected to lead to the achievement of an additional bilingual classroom with increased use of English at some points during the instructional process. This study aimed to investigate teachers' perceptions of implementing Content and Language Integrated Learning (CLIL) in primary schools. This study used a case study as the design of the research involving 25 primary school teachers from Global Inbyra School Tegal. Teachers’ interviews and observations were utilized as the instruments of the study. Research has shown that many teachers have implemented CLIL in the classroom and are fully aware of the importance of English and the integration of content and language, but lack knowledge of CLIL and lack the ability to implement a CLIL approach in the classroom. Observed not to use but yield to take a different approach. The results of this study demonstrate that CLIL teacher education programs need to implement this approach to increase teacher understanding and ensure better student learning outcomes in the classroom.